2019
DOI: 10.1021/acsabm.9b00600
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Chemo-Photothermal Suppression of Cancer by Melanin Decorated MoOx Nanosheets

Abstract: Two-dimensional (2D) nanomaterials able to effectively absorb near-infrared (NIR) radiation have shown considerable potential as multifunctional platforms in the treatment of cancer. Here we report a molybdenum dioxide (MoOx)-based system for synergistic chemo-and photothermal therapy of cancer. MoOx nanosheets were generated via a one-step hydrothermal route, grafted with polyethylene glycol (PEG), and decorated with melanin (Mel), with successful functionalization confirmed by IR spectroscopy. The mean diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…[38,39] Thus, the MoO 3-x nanomaterials were applied in photothermal removal of cancer. [40][41][42] The convenient way to obtain MoO 3-x nanomaterials is to separate from bulk oxide [17] MoO 3 powders with an exfoliation process, which is time consuming and low yield. Generally, the extraction of MoO 3-x nanoparticles can be classified as two categories: hydrothermal and chemical exfoliation.…”
Section: Introdutionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38,39] Thus, the MoO 3-x nanomaterials were applied in photothermal removal of cancer. [40][41][42] The convenient way to obtain MoO 3-x nanomaterials is to separate from bulk oxide [17] MoO 3 powders with an exfoliation process, which is time consuming and low yield. Generally, the extraction of MoO 3-x nanoparticles can be classified as two categories: hydrothermal and chemical exfoliation.…”
Section: Introdutionmentioning
confidence: 99%
“…But nanosheets obtained have poor hydrophilicity, which need to be modified by polyethylene glycol (PEG) to improve solubility. Xiao et al [41] reported a research work about the synthesis of strong photoluminescence MoO 3-x quantum dots via hydrogen peroxide (H 2 O 2 ) as the oxidant to inserted into molybdenum disulfide (MoS 2 ) powder. Compared with other papers, this method is without an external stimulus.…”
Section: Introdutionmentioning
confidence: 99%
“…The hydro/solvothermal synthesis method has been extensively used to prepare molybdenum oxide nanomaterials with different morphologies, such as nanodots (Figure 4A), nanoparticles, nanoribbons, nanosheets, nanospheres, and nanorings. [69,71,72,83,85,105,106,[159][160][161][162][163][164][165][166][167][168][169] As a typical example, Song et al reported the synthesis of molybdenum oxide nanomaterials with controlled morphologies by this method. [85] The mixed solution of (MoO 2 (OH)(OOH)) and PEG was treated in an autoclave at 90 °C for 12 h to obtain molybdenum oxide nanospheres.…”
Section: Hydrothermal/solvothermal Synthesismentioning
confidence: 99%
“…2D NMs are superior to other nanomaterials in terms of tumor identification drug delivery, and clinical treatment, providing a 3 powerful platform for enhanced medical precision. Common 2D NMs , such as ultra-thin graphene oxide [20], black phosphorus [21] and transition metal dihalides [22] have been used as drug carriers. However, these 2D NMs usually have some disadvantages, such as difficultsynthesis, limited loading capacity or poor biocompatibility, which limits their application in tumor targeted therapy [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chemotherapy, photothermal therapy (PTT) is also a widely used clinical treatment of cancer and is a novel and promising developing method for cancer treatment [22,38,39]. Compared with other cancer treatments, PTT is noninvasive and highly efficient, [40].…”
Section: Introductionmentioning
confidence: 99%